Long-Term Absolute Frequency Stabilization of a Hybrid-Integrated InP-Si3N4 Diode Laser - Albert van Rees; Lisa V. Winkler; Pierre Brochard; Dimitri Geskus; Peter J. M. van der Slot; Christian Nolleke; Klaus-J. Boller (IEEE Photonics Journal, 2023)
Hybrid integrated diode lasers based on combining semiconductor optical amplifiers with low-loss Si $_{3}$ N $_{4}$ -based feedback circuits enable great laser performance for advanced photonic circuits. In particular, using high-Q Si $_{3}$ N $_{4}$ ring resonators for frequency-selective feedback provides wide spectral coverage, mode-hop free tuning, and high frequency stability on short timescales, showing as ultra-narrow intrinsic linewidths. However, many applications also require long-term stability, which can be provided by locking the laser frequency to a suitable reference. We present the stabilization of a hybrid-integrated laser, which is widely tunable around the central wavelength of 1550 nm, to a fiber-based optical frequency discriminator (OFD) and to an acetylene absorption line. By locking the laser to the OFD, the laser's fractional frequency stability is improved down to $1.5· 10^{-12}$ over an averaging time of 0.5 ms. For absolute stability over longer times of several days, we successfully lock the laser frequency to an acetylene absorption line. This limits the frequency deviations of the laser to a range of less than 12 MHz over 5 days.